Mood Management as Mediator in Consumer Motivation and Impulsive Buying Relationship - Watang, Kirenius Conny Chapry; Miswanto, Miswanto (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
This study aims to test the relationship between consumer motivation and impulsive buying and the role of mood management as a mediator in the relationship between consumer motivation and impulsive buying. This study aims to determine the effect of hedonic motivation, cool motivation, socialization motivation on mood management and impulsive buying, especially for clothing products. Researchers used quantitative methods by collecting data through a questionnaire. The sample in this study were women who were at least 17 years old as many as 200 people. The finding of this research is that hedonic motivation, cool motivation, socialization motivation had a significant effect on mood management and impulsive buying. Hedonic motivation and socialization motivation have a significant effect on mood management, while cool motivation has no significant effect on mood management. Mood management has a significant effect on impulsive buying. Marketers need to study consumer motivation to increase sales through impulsive buying because consumer motivation and mood greatly influence purchasing decisions. Marketers need to pay attention to their marketing strategies to match the motivation of consumers who are the target market.